Causes influencing consumer purchasing satisfaction: a study on street food at Penang, Malaysia / Mohamad Zefry Suhaimi Ahmad Suraini ... [et al.] - Ahmad Suraini, Mohamad Zefry Suhaimi; Bibit, Nur Syahira; Abd. Aziz, Wan Siti Nor Azma; Mashuri, Mas Affandy; Mohamed Apandi, Siti Rohimi (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2023)
Penang is renowned for its unique history, thriving culture, exotic flora and fauna, rugged terrain, and numerous ethnic groupings. It is famous as "The Pearl of the Orient." Penang is Asia's most popular tourist destination and is recognized as a "food heaven," Street food sellers serve some of the world's best street food. This study aims to look into the factors influencing consumer satisfaction with street food purchases in Penang, Malaysia. This study uses a quantitative approach; the samples comprise customers who bought street food in Penang. This study used a quantitative methodology and a convenience sampling method, and the samples consisted of Penang customers who buy street food. The sample size was calculated using the G*Power app's estimation that the appropriate sample size for using simple linear regression is 129 respondents. The research reveals a positive relationship between food price, quality, hygiene, word of mouth, and consumer purchasing satisfaction. This research provides readers with extensive knowledge about consumer satisfaction that they can apply to their decision-making while purchasing food. The results of this study will hopefully help street food vendors identify possible surveys to market their stalls to become more popular and seek to meet client demand to optimize their revenue.